The affect of crafting : third millennium BCE copper arrowheads from Ganeshwar, Rajasthan - Rizvi, Uzma Z., 1973- (Archaeopress Publishing Ltd, 2018)
'The Affect of Crafting' presents an interrogation of materiality and crafting, a consideration of the situatedness of the technological practice of crafting itself, and the forms of relationships that exist between all things transformed in the act of crafting: bodies, minerals and landscapes.